Text Analysis: Microstructural Dimension of the Inside Out Animated Movie 2015 - Marsella Putri Indahsari; Evi Jovita Putri; Intan Firdaus (Institut Agama Islam Negeri Palopo, 2022)
This research is presented to discuss the script of “Inside Out” animated movie as the source of the data, which describes the narrative of a child who must adapt to her new environment and involves a lot of emotions. This study aims to reveal how the psychological message is conveyed in this movie script using the theory of van Dijk Design in Critical Discourse Analysis in Microstructural Text Level Analysis. Descriptive qualitative research method is used to explore and understand the central phenomenon, as well as content analysis techniques, which are used to interpret the messages contained in the movie script and the main ideas of the research topic. The result revealed: this movie is easily understood by children since the script writers use the basic phrases; humans have a very well-developed memory at the age of a child's golden age which can shape the child's personality and enter the subconscious memory, the human brain can also produce a thought or idea, including imagination. Based on the results, it can be concluded that human brain is able to record all memories that have occurred during human life and the human head can produce various kinds of emotions that appear according to the feelings or circumstances that are being experienced.